Angelica Sinensis Polysaccharide Prevents Hematopoietic Stem Cells Senescence in D-Galactose-Induced Aging Mouse Model - Mu, Xinyi (Stem Cells Int, 2017)
Age-related regression in hematopoietic stem/progenitor cells (HSC/HPCs) limits replenishment of the blood and immune system and hence contributes to hematopoietic diseases and declined immunity. In this study, we employed D-gal-induced aging mouse model and observed the antiaging effects of Angelica Sinensis Polysaccharide (ASP), a major active ingredient in dong quai (Chinese Angelica Sinensis), on the Sca-1(+) HSC/HPCs in vivo. ASP treatment prevents HSC/HPCs senescence with decreased AGEs levels in the serum, reduced SA-β-Gal positive cells, and promoted CFU-Mix formation in the D-gal administrated mouse. We further found that multiple mechanisms were involved: (1) ASP treatment prevented oxidative damage as total antioxidant capacity was increased and levels of reactive oxygen species (ROS), 8-OHdG, and 4-HNE were declined, (2) ASP reduced the expression of γ-H2A.X which is a DNA double strand breaks (DSBs) marker and decreased the subsequent ectopic expressions of effectors in p16(Ink4a)-RB and p19(Arf)-p21(Cip1/Waf) senescent pathways, and (3) ASP inhibited the excessive activation of Wnt/β-catenin signaling in aged HSC/HPCs, as the expressions of β-catenin, phospho-GSK-3β, and TCF-4 were decreased, and the cyto-nuclear translocation of β-catenin was inhibited. Moreover, compared with the positive control of Vitamin E, ASP exhibited a better antiaging effect and a weaker antioxidation ability, suggesting a novel protective role of ASP in the hematopoietic system.